One-dimensional Ti4O7 wave-absorbing agent, preparation method and application

By preparing one-dimensional Ti4O7 wave absorber and building a conductive absorption network using hydrothermal reaction and calcination methods, the problems of large density and poor absorption performance of traditional ceramic wave absorbing materials are solved, and high-efficiency electromagnetic wave absorption and low-density characteristics are achieved to meet the absorption Multiple performance requirements of wave materials.

CN119176580AActive Publication Date: 2024-12-24SHAANXI UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411385856.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-24
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Traditional ceramic wave absorbing materials have high density and poor absorption performance, which cannot meet the requirements of "thin, light, wide and strong", and lack effective conductive absorption network and multiple reflection scattering effects.

Method used

By preparing one-dimensional Ti4O7 absorber, using hydrothermal reaction and calcining methods, one-dimensional TiO2 and C are mixed and dispersed, a conductive absorption network is constructed, and impedance matching and absorption performance are optimized.

Benefits of technology

It realizes efficient electromagnetic wave absorption, reduces material density, enhances absorption capacity, meets the performance requirements of the absorbing materials of "thin, wide, light and strong", and optimizes impedance matching and energy loss.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119176580A_ABST
    Figure CN119176580A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of wave-absorbing materials, in particular to a one-dimensional Ti4O7 wave-absorbing agent as well as a preparation method and application of the one-dimensional Ti4O7 wave-absorbing agent. The preparation method comprises the following steps: mixing and dispersing one-dimensional TiO2 and C in a solvent, and drying to obtain a mixture; and calcining the mixture to obtain the one-dimensional Ti4O7 wave absorbing agent. According to the method, TiO2 of a one-dimensional structure and C are mixed and react to prepare the Ti4O7 wave-absorbing agent, the Ti4O7 wave-absorbing agent is prepared under the condition that the one-dimensional shape is reserved, and due to the fact that the one-dimensional Ti4O7 wave-absorbing agent has the high aspect ratio, an effective conductive absorption network can be constructed, an effective way can be provided for conductive dissipation of electromagnetic waves, meanwhile, the impedance matching level is optimized, and the wave-absorbing efficiency is improved. The electromagnetic wave-absorbing material has the advantages that the electromagnetic wave-absorbing material has a special structure, so that the electromagnetic wave-absorbing material has lower density, and the requirements of thin, wide, light and strong performances of the wave-absorbing material are met in the true sense. The problems that in the prior art, a wave-absorbing material is large in density and poor in wave-absorbing performance are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of wave absorbing material preparation, and specifically to a one-dimensional Ti 4 O 7 Wave absorbing agent, preparation method and application. Background Art

[0002] With the advancement of modern science and technology and the rapid development of the electronics industry, the application of various digital and high-frequency electronic devices has brought convenience to people's work and life, but also brought new environmental pollution - electromagnetic interference. The electromagnetic interference generated by electromagnetic radiation will affect the normal operation of electronic equipment, and the electromagnetic pollution caused by high-intensity electromagnetic radiation will also cause a certain degree of harm to human health.

[0003] Absorbing materials are a type of material that can convert incident electromagnetic energy into heat energy, or cause electromagnetic waves to interfere and attenuate. On the one hand, absorbing materials can absorb emitted detection radar waves, reduce the radar scattering cross section of the equipment, and thus play a radar stealth function; on the other hand, absorbing materials can shield electromagnetic radiation in industry and life, reducing the harm of electromagnetic waves.

[0004] Ideal electromagnetic wave absorbing materials require thin thickness, low density, wide absorption bandwidth and strong absorption capacity. The core of absorbing materials is absorbent materials with good electromagnetic wave absorption performance, which meet the requirements of "thin, wide, light and strong".

[0005] In order to obtain excellent absorbing performance, electromagnetic impedance matching and electromagnetic loss must be satisfied at the same time. Traditional absorbing materials are composed of ceramics, which have relatively low electrical conductivity and can only meet electromagnetic impedance matching, but cannot meet electromagnetic loss. Traditional absorbing materials have the following main defects: First, ceramic absorbing materials cannot construct an efficient conductive absorption network, which limits the conductive dissipation path of electromagnetic waves; second, ceramic absorbing materials usually do not have a network structure, which cannot promote the electromagnetic waves to produce a constraint effect in the network structure, and enhance absorption through multiple reflections and scattering; third, the low specific surface area and high density of ceramic materials greatly increase the amount of material used, resulting in absorbing materials being limited by weight and space; fourth, ceramic absorbing materials only have a single loss mechanism, which cannot compare with composite absorber materials with multiple loss mechanisms acting together. Therefore, traditional absorbing materials can no longer meet the requirements of "thin, light, wide and strong". Summary of the invention

[0006] Aiming at the problem that the absorbing material in the prior art has high density and poor absorbing performance, the present invention provides a one-dimensional Ti 4 O 7 Wave absorbing agent, preparation method and application.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a one-dimensional Ti 4 O 7 A method for preparing a wave absorbing agent comprises: Preparation of one-dimensional TiO 2 ; One-dimensional TiO 2 Mix with C, disperse in a solvent, and dry to obtain a mixture; The mixture is calcined to obtain a one-dimensional Ti 4 O 7 Wave absorber.

[0008] Furthermore, the preparation of one-dimensional TiO 2 The method is: TiO 2 The powder is dispersed in an alkaline solution to form a suspension; the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution with a concentration of 8 to 12 mol / L; The suspension is subjected to a hydrothermal reaction to obtain a hydrothermal reaction product; the hydrothermal reaction temperature is 160° C. to 185° C., and the reaction time is 18 to 24 hours; The hydrothermal reaction product is subjected to ion exchange to obtain titanic acid; Titanic acid is calcined to obtain one-dimensional TiO 2 .

[0009] Furthermore, the suspension contains TiO 2 The concentration of the powder is 18-22 g / L.

[0010] Furthermore, the method of subjecting the hydrothermal reaction product to ion exchange to obtain titanic acid is: The hydrothermal reaction product is ion exchanged with a hydrochloric acid solution with a concentration of 0.5 to 2 mol / L until the solution is neutral, and then washed with water and dried to obtain titanic acid.

[0011] Furthermore, the titanic acid is calcined to obtain a one-dimensional TiO 2 The calcination temperature is 400℃~500℃, and the calcination time is 2~3h.

[0012] Furthermore, the one-dimensional TiO 2 Mix with C, disperse in a solvent, and dry to obtain a mixture, wherein the solvent used is water or anhydrous ethanol.

[0013] Furthermore, the one-dimensional TiO 2 Mix with C and disperse in a solvent, dry, and obtain a mixture containing C and one-dimensional TiO 2 The mass ratio is (1~1.5):(2~2.5).

[0014] Further, the mixture is calcined to obtain a one-dimensional Ti 4 O 7 In the absorber, the calcination temperature is 1050°C to 1200°C, and the calcination time is 3 to 4 hours.

[0015] The present invention provides a one-dimensional Ti 4 O 7 The absorber is prepared by the above method.

[0016] As mentioned above, the one-dimensional 4 O 7 The application of absorbers in shielding electromagnetic radiation.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a one-dimensional Ti 4 O 7 The preparation method of the wave absorbing agent is to prepare a one-dimensional TiO 2 , and then the one-dimensional TiO 2 Mixed with C and dispersed in a solvent, dried and calcined to obtain a one-dimensional Ti 4 O 7 Absorber. Prepared one-dimensional Ti 4 O 7 Due to its high aspect ratio, the absorber allows the construction of an effective conductive absorption network, providing an effective way for the conductive dissipation of electromagnetic waves. At the same time, the conductive absorption network can also produce a confinement effect, enhancing the absorption of electromagnetic radiation by promoting multiple reflections and scattering within the network structure. In addition, the various gaps in the conductive network will reduce the effective dielectric constant of the material, making the gap between the magnetic permeability and the dielectric constant smaller, optimizing the impedance matching level, and increasing the possibility of effective electromagnetic absorption. At the same time, the high aspect ratio of the one-dimensional structure and the reduced material usage result in the light weight and small size of the absorber, making it an ideal choice for weight and space-constrained applications. The method is simple and easy to operate, and no toxic substances are used in the reaction process, with little waste and pollutants.

[0018] Through a simple hydrothermal reaction, the temperature of the hydrothermal reaction and the concentration of the alkaline solution are controlled to achieve one-dimensional TiO 2 The preparation method is simple and has strong operability.

[0019] The present invention also provides a one-dimensional Ti 4 O 7 The absorber is prepared by the above method. Compared with the traditional ceramic absorber, the one-dimensional Ti 4 O 7 The absorber has a smaller density, due to the Ti 4 O 7The oxygen vacancies in the absorber can provide electron transmission channels and have a higher dielectric constant and electromagnetic radiation absorption performance. Its one-dimensional structure can construct an effective conductive absorption network to further enhance the absorption of electromagnetic radiation, making it an ideal material for shielding electromagnetic radiation.

[0020] As mentioned above, the one-dimensional 4 O 7 The application of absorbent in shielding electromagnetic radiation is due to the one-dimensional Ti 4 O 7 The absorber has a higher dielectric constant, which means that more electric field energy can be stored inside the material, thereby enhancing the ability to absorb electromagnetic waves. It has a higher electrical conductivity, which helps to form higher energy loss, so that electromagnetic waves are effectively converted into energy in the form of heat energy and other forms inside the material and dissipated, making the shielding effect more ideal. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 A one-dimensional Ti 4 O 7 Schematic diagram of the process for preparing the absorber.

[0022] Figure 2 The one-dimensional TiO 2 Schematic diagram of the preparation method.

[0023] Figure 3 Ti prepared under different hydrothermal conditions in the embodiments of the present invention 4 O 7 SEM images of the absorber, where a, b, c and d are Ti prepared under the conditions of 160°C, alkali solution concentrations of 6 mol / L, 8 mol / L / 10 mol / L and 12 mol / L, and hydrothermal reaction for 18 h. 4 O 7 SEM images of the absorber; e, f, g and h are Ti prepared under the conditions of 180℃, 6mol / L, 8mol / L / 10mol / L and 12mol / L alkaline solutions, and 24h hydrothermal reaction. 4 O 7 SEM image of the absorber.

[0024] Figure 4 The hydrothermal temperature in the present invention is 160°C, the hydrothermal time is 18h, and the Ti prepared under different concentration conditions is 4 O 7 The curve of the dielectric parameters of the absorber changing with frequency, where a is the real part curve, b is the imaginary part curve, and c is the loss tangent curve.

[0025] Figure 5In the embodiment of the present invention, the hydrothermal temperature is 180°C, the hydrothermal time is 24h, and the Ti prepared under different concentration conditions 4 O 7 The curve of the dielectric parameters of the absorber changing with frequency, where a is the real part curve, b is the imaginary part curve, and c is the loss tangent curve.

[0026] Figure 6 The Ti prepared in Example 2 of the present invention at a hydrothermal temperature of 180° C. and a hydrothermal time of 24 h 4 O 7 The relationship between reflection loss and frequency and the three-dimensional simulation diagram of reflection loss (RL), where a is the curve diagram of the relationship between reflection loss and frequency, and b is the three-dimensional simulation diagram of reflection loss (RL). DETAILED DESCRIPTION

[0027] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0028] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0029] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0030] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0031] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0032] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0033] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0034] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0035] The invention discloses a one-dimensional Ti 4 O 7 The preparation method of the absorbent is as follows: Figure 1 ,include: S1: Preparation of one-dimensional TiO 2 , specifically: S1.1: TiO 2 The powder is dispersed in an alkaline solution to form a suspension: the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution with a concentration of 8 to 12 mol / L, preferably a sodium hydroxide solution of 10 to 12 mol / L, and more preferably a sodium hydroxide solution of 12 mol / L; the suspension contains TiO 2 The concentration of the powder is 18-22 g / L, preferably 20 g / L; S1.2: subjecting the suspension to a hydrothermal reaction to obtain a hydrothermal reaction product: the hydrothermal reaction temperature is 160°C to 185°C, the reaction time is 18 to 24 hours, preferably 170°C to 185°C, 20 to 24 hours, more preferably 180°C to 185°C, 20 to 24 hours; S1.3: performing ion exchange on the hydrothermal reaction product to obtain titanic acid: using a hydrochloric acid solution with a concentration of 0.5 to 2 mol / L to perform ion exchange on the hydrothermal reaction product until the solution is neutral, washing with water, and drying to obtain titanic acid. Preferably, a hydrochloric acid solution with a concentration of 1 mol / L is used to perform ion exchange on the hydrothermal reaction product; S1.4: Calcinate titanic acid to obtain one-dimensional TiO 2 : Calcination temperature is 400°C to 500°C, calcination time is 2 to 3h, preferably 450°C, calcination for 3h; S2: One-dimensional TiO 2 and C are mixed and dispersed in a solvent, and dried to obtain a mixture: the solvent used is water or anhydrous ethanol, preferably anhydrous ethanol; C and one-dimensional TiO 2 The mass ratio is (1-1.5): (2-2.5), preferably 1:2 S3: calcining the mixture to obtain a one-dimensional Ti 4 O 7 Wave absorber: The calcination temperature is 1050°C to 1200°C, and the calcination time is 3 to 4 hours, preferably 1150°C to 1200°C, 3 hours.

[0036] Example 1 Prepare sodium hydroxide solutions with concentrations of 6 mol / L, 8 mol / L, 10 mol / L and 12 mol / L respectively; In 50 mL of the above sodium hydroxide solution, 1 g TiO 2 The powder was stirred for 2 hours to obtain a suspension; the suspension was transferred to a hydrothermal reactor and reacted for 18 hours at 160°C to obtain a hydrothermal reaction product; The obtained hydrothermal reaction product was adjusted to pH 7 with a 1 mol / L dilute hydrochloric acid solution, and then stirred for 8 hours to perform sufficient ion exchange. Excess HCl was washed away with deionized water by suction filtration, and the obtained product was dried at 80° C. to obtain titanic acid.

[0037] The obtained titanic acid was calcined in a box furnace at 450 °C for 2 h to convert it into a one-dimensional TiO 2 .

[0038] In the C and one-dimensional TiO 2 Weigh one-dimensional TiO 2 and carbon black, add anhydrous ethanol, mix well, ultrasonicate for 30 min, centrifuge, and then put the mixture obtained by centrifugation into an oven at 60°C for 8 h to obtain a mixture; The mixture was placed in a vacuum tube furnace and calcined in a nitrogen atmosphere at a temperature of 1150°C for 3 h to obtain Ti 4 O 7 Wave absorbing material.

[0039] Example 2 Prepare sodium hydroxide solutions with concentrations of 6 mol / L, 8 mol / L, 10 mol / L and 12 mol / L respectively; In 50 mL of the above sodium hydroxide solution, 1 g TiO 2The powder was stirred for 2 hours to obtain a suspension; the suspension was transferred to a hydrothermal reactor and reacted at 180°C for 24 hours to obtain a hydrothermal reaction product; The obtained hydrothermal reaction product was adjusted to pH 7 with a 1 mol / L dilute hydrochloric acid solution, and then stirred for 8 hours to perform sufficient ion exchange. Excess HCl was washed away with deionized water by suction filtration, and the obtained product was dried at 80° C. to obtain titanic acid.

[0040] The obtained titanic acid was calcined in a box furnace at 450 °C for 2 h to convert it into a one-dimensional TiO 2 .

[0041] In the C and one-dimensional TiO 2 Weigh one-dimensional TiO 2 and carbon black, add anhydrous ethanol, mix well, ultrasonicate for 30 min, centrifuge, and then put the mixture obtained by centrifugation into an oven at 60°C for 8 h to obtain a mixture; The mixture was placed in a vacuum tube furnace and calcined in a nitrogen atmosphere at a temperature of 1150°C for 3 h to obtain Ti 4 O 7 Wave absorbing material.

[0042] The various Ti prepared in Examples 1 and 2 4 O 7 The absorber was tested by SEM, and the results are shown in Figure 3 As can be seen from the figure, when the hydrothermal time is 18h and the hydrothermal temperature is 160℃, with the increase of NaOH concentration, Ti 4 O 7 The morphology of the absorber gradually changed from granular to one-dimensional tubular structure. When the hydrothermal time was 24h, the hydrothermal temperature was 180℃, and the NaOH concentration was 6 mol / L and 8 mol / L, Ti 4 O 7 In the SEM image of the absorber, it can be observed that there are many one-dimensional tubular microcrystalline particles showing extended, multi-branched and mixed morphologies. When the NaOH concentration is 10 mol / L and 12 mol / L, the tubular microcrystalline particles are bonded to each other and transformed into bundled microcrystalline particles. 2 Preparation of Ti by high temperature redox reaction with carbon black 4 O 7 The obtained product retains TiO 2 The original one-dimensional morphology, and the one-dimensional structure of the product is more obvious when the hydrothermal time is 24 h and the hydrothermal temperature is 180℃.

[0043] See also Figure 4 , for the test type Ti 4 O7 The influence of the morphology of the absorbent on the electromagnetic radiation absorption performance, Ti prepared under different conditions in Example 1 4 O 7 The dielectric constant performance test was carried out and it was found that the Ti prepared at a hydrothermal temperature of 160 ° C and a hydrothermal time of 18 h 4 O 7 The real part of the dielectric constant of the absorber decreases gradually with the increase of frequency, which is consistent with its granular Ti 4 O 7 The relationship between the real part of the dielectric constant and the frequency is consistent. When the NaOH concentration is 10mol / L and 12mol / L, the Ti 4 O 7 The real part of the dielectric constant of the absorber is compared with that of granular Ti 4 O 7 This is due to the one-dimensional Ti 4 O 7 The conductive network is formed by interconnecting with each other, which further improves the conductivity of the material. When the NaOH concentration is 6 mol / L and 8 mol / L, Ti 4 O 7 The imaginary part of the dielectric constant and its relationship with frequency are similar to those of granular Ti 4 O 7 This is because the Ti prepared under this condition 4 O 7 It does not have a one-dimensional structure and is still granular. When the NaOH concentration is 10 mol / L and 12 mol / L, Ti 4 O 7 The imaginary part of the dielectric constant is compared with that of granular Ti 4 O 7 It has a significant increase, indicating that the one-dimensional structure has a stronger loss capacity for electromagnetic waves. It can be seen that when the hydrothermal reaction condition is 160°C, the concentration of the alkaline solution in the hydrothermal reaction is preferably 10-12 mol / L, and more preferably 12 mol / L.

[0044] See also Figure 5 , for the test type Ti 4 O 7 The influence of the morphology of the absorbent on the electromagnetic radiation absorption performance, Ti prepared under different conditions in Example 2 4 O 7 The dielectric constant performance test was carried out and it was found that under the reaction conditions of 180℃ and 24h, the prepared Ti 4 O 7 Real part of dielectric constant and granular Ti 4 O 7When the concentration of NaOH is 8mol / L, 10mol / L and 12mol / L, Ti 4 O 7 The real part of the dielectric constant is compared with that of granular Ti 4 O 7 There is a significant increase, while the Ti 4 O 7 The real part of the dielectric constant decreases instead, which is speculated to be due to the one-dimensional Ti 4 O 7 Poor crystallinity leads to decreased dielectric properties. It can be seen that under the condition of 180°C, the concentration of the alkaline solution in the hydrothermal reaction is preferably 8 to 12 mol / L, and more preferably 12 mol / L.

[0045] See also Figure 6 The Ti prepared in Example 2 was prepared by hydrothermal reaction at 180°C, with a sodium hydroxide concentration of 8 mol / L and a reaction time of 24 h. 4 O 7 The absorbent was tested for its absorbing performance and the results showed that: Ti 4 O 7 The absorber is in the X-band (2-18 GHz): the optimal thickness of the sample is 3.23 mm, the absorption peak appears at a frequency of 6.975 GHz, and the reflection loss is -68.35 dB. It can be seen that the one-dimensional Ti prepared by the present invention 4 O 7 The absorber has very good electromagnetic radiation absorption function.

[0046] A one-dimensional shape 4 O 7 The absorber is prepared by the above method. Compared with the traditional ceramic absorber, the one-dimensional Ti 4 O 7 The absorber has a smaller density, due to the Ti 4 O 7 The oxygen vacancies in the absorber can provide electron transmission channels and have a higher dielectric constant and electromagnetic radiation absorption performance. Its one-dimensional structure can construct an effective conductive absorption network to further enhance the absorption of electromagnetic radiation, making it an ideal material for shielding electromagnetic radiation.

[0047] As mentioned above, the one-dimensional 4 O 7 The application of wave absorbers in shielding electromagnetic radiation. 4 O 7The absorber has a higher dielectric constant, which means that more electric field energy can be stored inside the material, thereby enhancing the ability to absorb electromagnetic waves. It has a higher electrical conductivity, which helps to form higher energy loss, so that electromagnetic waves are effectively converted into energy in the form of heat energy and other forms inside the material and dissipated, making the shielding effect more ideal.

[0048] In summary, the present invention provides a one-dimensional Ti 4 O 7 Wave absorbing agent, preparation method and application thereof, by using one-dimensional structure TiO 2 Mixed with C to prepare Ti 4 O 7 The absorber makes the prepared one-dimensional Ti 4 O 7 Due to its high aspect ratio, the absorber allows the construction of an effective conductive absorption network, providing an effective way for the conductive dissipation of electromagnetic waves. In addition, the various gaps in the conductive network will reduce the effective dielectric constant of the material, making the gap between the magnetic permeability and the dielectric constant smaller, optimizing the impedance matching level, and increasing the possibility of effective electromagnetic absorption. Due to its special structure, the material has a smaller density, which truly meets the performance requirements of the absorbing material such as "thin, wide, light, and strong".

[0049] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A method for preparing a one-dimensional Ti4O7 absorber, characterized in that: include: Preparation of one-dimensional TiO2; Mixing one-dimensional TiO2 and C in a solvent, dispersing the mixture, and drying the mixture to obtain a mixture; The mixture is calcined to obtain a one-dimensional Ti4O7 absorber.

2. The method for preparing the one-dimensional Ti4O7 absorber according to claim 1, characterized in that: The method for preparing one-dimensional TiO2 is: Dispersing TiO2 powder in an alkaline solution to form a suspension; the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution with a concentration of 8 to 12 mol / L; The suspension is subjected to a hydrothermal reaction to obtain a hydrothermal reaction product; the hydrothermal reaction temperature is 160° C. to 185° C., and the reaction time is 18 to 24 hours; The hydrothermal reaction product is subjected to ion exchange to obtain titanic acid; Titanic acid is calcined to obtain one-dimensional TiO2.

3. The method for preparing the one-dimensional Ti4O7 absorber according to claim 2, characterized in that: The concentration of TiO2 powder in the suspension is 18-22 g / L.

4. The method for preparing the one-dimensional Ti4O7 absorber according to claim 2, characterized in that: The method of subjecting the hydrothermal reaction product to ion exchange to obtain titanic acid is: The hydrothermal reaction product is ion exchanged with a hydrochloric acid solution with a concentration of 0.5 to 2 mol / L until the solution is neutral, and then washed with water and dried to obtain titanic acid.

5. The method for preparing the one-dimensional Ti4O7 absorber according to claim 2, characterized in that: The calcination temperature of calcining titanic acid to obtain one-dimensional TiO2 is 400°C to 500°C, and the calcination time is 2 to 3 hours.

6. The method for preparing the one-dimensional Ti4O7 absorber according to claim 1, characterized in that: The one-dimensional TiO2 and C are mixed and dispersed in a solvent, and dried to obtain a mixture, and the solvent used is water or anhydrous ethanol.

7. The method for preparing the one-dimensional Ti4O7 absorber according to claim 1, characterized in that: The one-dimensional TiO2 and C are mixed and dispersed in a solvent, and dried to obtain a mixture in which the mass ratio of C to the one-dimensional TiO2 is (1-1.5): (2-2.5).

8. The method for preparing the one-dimensional Ti4O7 absorber according to any one of claims 1 to 7, characterized in that: The mixture is calcined to obtain a one-dimensional Ti4O7 absorber, the calcination temperature is 1050°C to 1200°C, and the calcination time is 3 to 4 hours.

9. A one-dimensional Ti4O7 absorber, characterized in that: Prepared by the method described in any one of claims 1 to 8.

10. Use of the one-dimensional Ti4O7 absorber as claimed in claim 9 in shielding electromagnetic radiation.

Citation Information

Patent Citations

  • Titanium dioxide nanoribbon photocatalyst and preparation and applications thereof

    CN103801277A

  • Preparation method for Ti4O7 nanometer fiber

    CN105155039A

  • Ti4O7 nano material as well as preparation method thereof and use thereof

    CN108862377A

  • Preparation method of TiO2 material with oxygen vacancies

    CN110937628A

  • Method for preparing high-purity-phase Ti4O7 nano-material in inert atmosphere through one-step technology

    CN111115681A